Allergens and their associated small molecule ligands—their dual role in sensitization. Issue 8 (2nd May 2021) - Chruszcz, Maksymilian; Chew, Fook Tim; Hoffmann‐Sommergruber, Karin; Hurlburt, Barry K.; Mueller, Geoffrey A.; Pomés, Anna; Rouvinen, Juha; Villalba, Mayte; Wöhrl, Birgitta M.; Breiteneder, Heimo
Abstract: Many allergens feature hydrophobic cavities that allow the binding of primarily hydrophobic small‐molecule ligands. Ligand‐binding specificities can be strict or promiscuous. Serum albumins from mammals and birds can assume multiple conformations that facilitate the binding of a broad spectrum of compounds. Pollen and plant food allergens of the family 10 of pathogenesis‐related proteins bind a variety of small molecules such as glycosylated flavonoid derivatives, flavonoids, cytokinins, and steroids in vitro. However, their natural ligand binding was reported to be highly specific. Insect and mammalian lipocalins transport odorants, pheromones, catecholamines, and fatty acids with a similar level of specificity, while the food allergen β‐lactoglobulin from cow's milk is notably more promiscuous. Non‐specific lipid transfer proteins from pollen and plant foods bind a wide variety of lipids, from phospholipids to fatty acids, as well as sterols and prostaglandin B2, aided by the high plasticity and flexibility displayed by their lipid‐binding cavities. Ligands increase the stability of allergens to thermal and/or proteolytic degradation. They can also act as immunomodulatory agents that favor a Th2 polarization. In summary, ligand‐binding allergens expose the immune system to a variety of biologically active compounds whose impact on the sensitization process has not been well studied thus far.